Naturalistic second language acquisition: a case of adoption in Italy - Ramonaitė, Jogilė Teresa (Taikomoji kalbotyra, 2013)
The functional approach to the interlanguage of spontaneous learners of L2 helps identify that from the very beginning without yet possessing many resources of the target language the speaker makes a systemic use of them. When acquiring a language in a natural environment the effectiveness of communication is of vital importance to the speaker because he or she must start interacting without yet having acquired many of the elements of the structure of the target language. A second language learner makes use of the cognitive resources already in possession and therefore when beginning to use the new language invokes the universal pragmatic principles for utterance organization such as word order. A very important step in L2 acquisition is the appearance of the predicate in the interlanguage of the learner because then the utterances of the speaker are constructed following also the semantic-syntactic principles. This variety of the learnerʼs interlanguage, called the basic variety, is in principle sufficient for elementary communication and the development of interlanguage in the morphological perspective for some learners fossilizes in this variety. In due time and given favourable conditions, the interlanguage of the learner can move on to the so-called post-basic variety that sees the formation of a system approaching that of the target language and the principles of utterance organization previously used are gradually replaced by syntactic principles characteristic of the specific target language. The situation of international adoption presents favourable conditions for the language acquisition of younger and also older children. The article offers examples and analysis of the linguistic behaviour of an over 11-year-old Lithuanian girl adopted to Italy. Her linguistic behaviour has been meticulously observed and recorded for a year after the adoption starting from the very first contact with the new language. The analysis shows that the structure of the target language is acquired according to the universal model proceeding from simple to more complex forms. However the situation in which the acquisition takes place determines the rapidity of L2 acquisition and a very advanced level after a year in the new country. The observed girl reaches the basic variety after having spent only a month surrounded by the new language and one month later her interlanguage demonstrates clear signs of morphological sensitivity and the interlanguage system heading towards that of the target language. After a year in the country the entire Italian verb system is in place, including the most complex parts of it. Moreover, the girl makes use of those system elements that are optional, in a way that native speakers are able to do.